A disorder-free conformation boosts phonon and charge transfer in an electron-deficient-core-based non-fullerene acceptor. Issue 17 (22nd April 2020) - Zhang, Chujun; Yuan, Jun; Chiu, Ka Lok; Yin, Hang; Liu, Weifang; Zheng, Guanhaojie; Ho, Johnny Ka Wai; Huang, Suzhen; Yu, Gaoxing; Gao, Feng; Zou, Yingping; So, Shu Kong
Abstract : A disorder-free molecular conformation caused by alkyl side chains facilitates electron transport, heat transfer and reduces electronic disorder. Abstract : Electron acceptors with a chemical structure of A–DA′D–A (in which A denotes an acceptor moiety and D a donor moiety) are rapidly gaining prominence in organic solar cells (OSCs). In OSCs containing these acceptors, record power conversion efficiencies (PCEs) exceeding 16% are now widely reported. Despite encouraging advances related to new material designs and PCEs, the fundamental interplay between molecular structure and device performance still requires further understanding. Here, we choose two model A–DA′D–A type acceptors, Y3 and Y18, that have almost identical structures, and examine how the presence of two extra alkyl chains (attached to the periphery of the DA′D core) in Y18 impacts on its solid state properties and device performance. These properties include: (i) charge transport; (ii) heat transfer; and (iii) electronic disorder. We found that bulk-heterojunction (BHJ) OSCs that use Y3 and Y18 have markedly different PCEs of ∼13 and 16%, respectively. Correspondingly, the BHJ containing Y18 possesses more efficient phonon transfer and charge transport and suppressed electronic disorder. Among these properties, the extremely low Urbach energy ( E U ) of 23 meV in Y18 stands out because this is even below the thermal energy (∼26 meV), which sets the electronic disorder limit at room temperature. With all these contrasting results, a simple molecular model can be rationalized in which the extra alkyl chains in Y18 help to suppress the formation of rotamers, endowing it with a disorder free molecular conformation and remarkable solid state properties. This work provides not only a new physical understanding of the effect of alkyl chains in organic semiconductors, but also new ideas for the synthesis of novel materials that can be adopted for use in high-performance OSCs.